The Dilemma of Basia's Pendant: European Community Design and the Protection of an Artist's Creations and Intellectual Property - Richard Hunter; John Shannon; Hector Lozada; Barbara Rivolta (The Institute of Academic Research and Publication (IARP), 2021)
This article is a description of the process of protecting a designer’s intellectual property through registration with the European Union Intellectual Property Office or EUIPO or through relying on the status of an Unregistered Community Design. The article discusses the registration process as well as the process of invalidation and considers issues relating to the enforcement of rights. Finally, the article focuses on whether a complaint about possible copyright infringement may be lodged against an online retailer or an online e-commerce website that offers unlicensed sales or unauthorized copies of a designer’s design by utilizing the descriptions or photographs of the designer.